2019
DOI: 10.1037/xhp0000659
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention in explaining the no-go devaluation effect: Effects on appetitive food items.

Abstract: Evaluations of stimuli can be changed by simple motor responses such that stimuli to which responses are consistently withheld tend to be evaluated less positively than other stimuli. The exact mechanism that underlies this no-go devaluation effect is still unknown. Here we examine whether attention to the stimuli during training contributes to the devaluation effect. Participants received a go/no-go training in which 2 go items or 2 no-go items were simultaneously presented, and attention to 1 of the items wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…The fact that the reported variability in previous experiences with food was related to the variability of evaluations sheds light on the question why evaluations in psychological experiments often show variability even on very short time scales and without contextual changes (Chen et al, 2016; Folke et al, 2016; Quandt et al, 2019; Schonberg et al, 2014). This has important theoretical and practical implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the reported variability in previous experiences with food was related to the variability of evaluations sheds light on the question why evaluations in psychological experiments often show variability even on very short time scales and without contextual changes (Chen et al, 2016; Folke et al, 2016; Quandt et al, 2019; Schonberg et al, 2014). This has important theoretical and practical implications.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate this experience, we asked them to build a distribution from 20 hypothetical consumptions of each food item We reduced the number of points to be distributed to 20 (as opposed to 100 in Experiments 1 and 2) to reduce the duration of the task with 24 food pictures. The range of this scale was chosen in line with prior research on food evaluations (Chen et al, 2016(Chen et al, , 2019Quandt et al, 2019) Binary Choice Task. Due to time constraints, we could not present participants with all possible combinations of the 24 food items.…”
Section: Methodsmentioning
confidence: 99%
“…Third, for mediation to take place, we need evidence that we can manipulate the mediator and that it has the predicted effect (Bullock et al, 2010). Otherwise, confounding variables (e.g., attention; Quandt et al, 2019) might bias the results. In our case, we showed that we could manipulate the mediator in filler trials.…”
Section: Discussionmentioning
confidence: 99%
“…According to this account, people devalue distracting objects so that they do not interfere with the task. No-go objects may be considered distractors, particularly when no-go objects are attractive, because they interfere with the goal of responding (Quandt, Holland, Chen, & Veling, 2019). Finally, according the behavior stimulus interaction theory (Chen et al, 2016; Veling, Holland, & van Knippenberg, 2008), inhibition of a response to an attractive object leads to a response conflict, which is accompanied by negative affect that becomes attached to the attractive object.…”
mentioning
confidence: 99%
“…Moreover, the continuous withholding of responses to attractive cues may also produce conflicts and negative affect, that eventually may lead to devaluation of the initial targeted cues. To date, several studies have shown evidence for lower evaluations of trained No-Go compared to Go and/or untrained pictures, interpreted as evidence for devaluation (Chen et al, 2016(Chen et al, , 2018aHouben et al, 2012;Quandt et al, 2019;Scholten et al, 2019;Veling et al, 2013). However, some recent studies found that the effects of Go/No-Go training were smaller for rewarding stimuli and stronger for aversive or neutral stimuli (Chen et al, 2019;De Pretto et al, 2019), which is in apparent contrast with a cue-devaluation mechanism of rewarding cues.…”
Section: Go/no-go Tasksmentioning
confidence: 98%